2021
DOI: 10.1097/htr.0000000000000678
|View full text |Cite
|
Sign up to set email alerts
|

Poor Parental Supervision Associated With Traumatic Brain Injury and Reactive Aggression in Young Offenders

Abstract: Objective: To establish whether poor parental supervision is associated with head injury and self-reported reactive aggression (ie, aggression in response to perceived provocation or threat) in adolescents in a Young Offender's Institute, by examining correlations between these variables. Understanding this population is important, as they are at a key pivotal age for intervention to prevent lifelong reoffending. Methods: Ninety-six male participants aged 16 to 18 years were recruited from a UK Young Offender'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Structural equation modelling has shown that childhood TBI mediates the relationship between poor educational attainment and o ending behaviour in adolescents, showing the signi cance of addressing TBI related-needs earlier in the education system (Clasby et al, 2020). Parenting practices can in uence outcomes following childhood TBI, and poor parental supervision is associated with both more severe TBI and higher levels of reactive aggression in young o enders (Kent et al, 2021). TBI can exacerbate existing di culties with maturity and social development, and greatly reduce an individual's ability to cope with, and adapt to, the social and academic pressures of school (Williams et al, 2020).…”
Section: Poverty and Educationmentioning
confidence: 99%
“…Structural equation modelling has shown that childhood TBI mediates the relationship between poor educational attainment and o ending behaviour in adolescents, showing the signi cance of addressing TBI related-needs earlier in the education system (Clasby et al, 2020). Parenting practices can in uence outcomes following childhood TBI, and poor parental supervision is associated with both more severe TBI and higher levels of reactive aggression in young o enders (Kent et al, 2021). TBI can exacerbate existing di culties with maturity and social development, and greatly reduce an individual's ability to cope with, and adapt to, the social and academic pressures of school (Williams et al, 2020).…”
Section: Poverty and Educationmentioning
confidence: 99%